Stabilising sleep for patients admitted at acute crisis to a psychiatric hospital (OWLS): an assessor-blind pilot randomised controlled trial - Sheaves, B; Freeman, D; Isham, L; McInerney, J; Nickless, A; Yu, L; Rek, S; Bradley, J; Reeve, S; Attard, C; Espie, C; Foster, R; et al. (Cambridge University Press, 2017)
Background When patients are admitted onto psychiatric wards, sleep problems are highly prevalent. We carried out the first trial testing a psychological sleep treatment at acute admission (Oxford Ward sLeep Solution, OWLS). Methods This assessor-blind parallel-group pilot trial randomised patients to receive sleep treatment at acute crisis [STAC, plus standard care (SC)], or SC alone (1 : 1). STAC included cognitive–behavioural therapy (CBT) for insomnia, sleep monitoring and light/dark exposure for circadian entrainment, delivered over 2 weeks. Assessments took place at 0, 2, 4 and 12 weeks. Feasibility outcomes assessed recruitment, retention of participants and uptake of the therapy. Primary efficacy outcomes were the Insomnia Severity Index and Warwick–Edinburgh Mental Wellbeing Scale at week 2. Analyses were intention-to-treat, estimating treatment effect with 95% confidence intervals. Results Between October 2015 and July 2016, 40 participants were recruited (from 43 assessed eligible). All participants offered STAC completed treatment (mean sessions received = 8.6, s.d. = 1.5). All participants completed the primary end point. Compared with SC, STAC led to large effect size (ES) reductions in insomnia at week 2 (adjusted mean difference −4.6, 95% CI −7.7 to −1.4, ES −0.9), a small improvement in psychological wellbeing (adjusted mean difference 3.7, 95% CI −2.8 to 10.1, ES 0.3) and patients were discharged 8.5 days earlier. One patient in the STAC group had an adverse event, unrelated to participation. Conclusions In this challenging environment for research, the trial was feasible. Therapy uptake was high. STAC may be a highly effective treatment for sleep disturbance on wards with potential wider benefits on wellbeing and admission length.